Belgium & Luxembourg [videorecording (DVD)] - Delaney, Francis (Pilot Productions, 2007)
Katy Haswell visits Belgium and Luxembourg, two European countries small in stature but large in attractions, such as Antwerp, Bruges, Brussels, and the site of the battle of Waterloo, then Luxembourg in time to take part in the National Day festivities.